Identification of new cases of tuberculosis during the COVID-19 pandemic using model strategic management - Eppy Setiyowati; Umi Hanik; Ni Njoman Juliasih; Priyo Susilo (PAGEPress Publications, 2023)
Introduction: Tuberculosis (TB) is a world health problem that causes the third-largest death after cardiovascular and respiratory diseases. One of the causes of transmission of environmental factors is controlling the mobilization of individuals suffering from tuberculosis. This research aims to develop a strategic model of finding new TB cases based on region. Method: This descriptive research utilizes primary and secondary data. Variables consist of geographical and demographic characteristics, resources, tuberculosis prevalence, and indicators of tuberculosis response processes. The TB management planning model document is based on the experiences of health centers Perak Timur, Wonokromo, and Siwalankerto in maximizing TB case detection. Results: The management model outlines policies and procedures based on the variables. For example, the detection of new TB patients became a priority at the health center in Perak Timur. In contrast, the health center in Wonokromo focused on developing cadres and private practice physicians. Conclusions: This research provides an overview of the aspects that need attention and improvement by discovering different new cases in each region.